PEMROGRAMAN LOGIC PANEL PADA TRAINING UNIT VERTICAL REVOLVING HANDLING DEVICE - , RASYID SETIAWAN; , Radhian Krisnaputra, ST., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Control system is a part of components that working together under the direction of some machine intelligence. Forming device simulation is an example for work simulation in industry. It simulation in Training Kit Logic Panel (LP) is a simulation which is created to simulator in industry automation. This tool is completed with Logic Panel (LP) as the brain. The main function of making this equipment is used to simulation a forming device. To finish this final task, there are some methods have been done such as collecting some data related with this task, make a program and also the electric connection structure. The result of this task that Simulator Training Kit Logic Panel (LP) can be used and fully helps student to study comfortably. So, the student will understand easily.